2019
DOI: 10.1002/bit.27083
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic neuronal stimulation promotes axon outgrowth and myelination of motor neurons in a three‐dimensional motor neuron–Schwann cell coculture model on a microfluidic biochip

Abstract: Axonal regeneration and remyelination of peripheral motor neurons (MNs) are critical for restoring neuromuscular motor function after injury or peripheral neuropathy. We examined whether optogenetically mediated light stimulation (OMLS) could enhance the axon outgrowth and myelination of MNs using threedimensional motor neuron-Schwann cell (MN-SC) coculture on a microfluidic biochip. The biochip was designed to allow SCs to interact with the axons of MNs, while preventing direct contact between SCs and the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 47 publications
4
25
0
Order By: Relevance
“…; p = 0.1157, unpaired t-test; Figure 4d). These results are in line with recently published data by Hyung et al (2019) on MN responses to optical stimulation in 3D hydrogels [49].…”
Section: Optogenetic Modulation Of Mn Activity Increases Axonal Outgrsupporting
confidence: 93%
See 1 more Smart Citation
“…; p = 0.1157, unpaired t-test; Figure 4d). These results are in line with recently published data by Hyung et al (2019) on MN responses to optical stimulation in 3D hydrogels [49].…”
Section: Optogenetic Modulation Of Mn Activity Increases Axonal Outgrsupporting
confidence: 93%
“…By taking advantage of an approach combining microfluidics, in vitro axotomy, and optogenetics, this study suggests the previously undescribed role of muscular activity through a paracrine mechanism to promote axonal regrowth of MNs after injury. Specifically, we found that optogenetic modulation of neuronal activity induces a ≈2-fold increase (although non-statistically significant) in axonal regrowth, similar to what was observed by [49]. In addition, we determined that modulating C2C12 contractility after MN axotomy by optogenetics induces an increase in the expression and release of LIF and GDNF, which in turn increases the regrowth of MN axons.…”
Section: Discussionsupporting
confidence: 69%
“…SC suspension was seeded on coverslips pre-coated with 10 μg/mL poly-Dlysine (PDL, Sigma). After 3 days, complement-mediated cytolysis was performed to remove fibroblasts from the SC culture, as previously described [18,20]. Briefly, cells were treated with DMEM containing 20 mM hydroxyethyl-piperazineethanesulfonic acid (HEPES) buffer (T and I), 10% FBS, 4 mM L-gln, and 1% P/S) for 5 min before washing with Ca2 + -and Mg2 +free Hank's balanced salt solution (HBSS, Invitrogen) containing 20 mM HEPES.…”
Section: Primary Sc Culturementioning
confidence: 99%
“…MN culturing was performed as described previously [18,20]. 12 fetuses) were harvested in Ca2 + -and Mg2 + -free HBSS containing 1% Toll-like receptor (TLR) trypsin (Worthington) for 15 min at 37°C, followed by treatment with 1% trypsin inhibitor (Sigma).…”
Section: Primary Mn Cell Culturementioning
confidence: 99%
“…Furthermore, using a thermonociception-based behavioral recovery assay, we found that optoRaf and optoAKT activation led to effective axon regeneration as well as functional recovery after central nervous system (CNS) injury. We note that most of the previous optogenetic control of neural repair studies were based on channelrhodopsion in C. elegans ( Sun et al, 2014 ), mouse DRG culture ( Park et al, 2015a ) or motor neuron-schwann cell co-culture ( Hyung et al, 2019 ). Another study used blue-light activatable adenylyl cyclase bPAC to stimulate neural repair in mouse refractory axons ( Xiao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%